Particleboard characterization using sawdust from sengon wood, mahogany wood, bayur wood, and rice husk ash as composite fillers. Issue 1 (December 2020) - Sunardi,; Lusiani, Rina; Saefuloh, Iman; Listijorini, Erny; Eka Sumarna, Anggit; Fawaid, Moh.; Meliana, Yenny
Abstract: Banten Province, Indonesia, has abundant natural resources. Waste from processing natural resources has not been utilized maximally. Several types of wood and plants used in this study were sengon ( albizia Chinensis ), bayur ( pterspermum javanicum ), mahogany (Swietenia mahogany) and rice husk ash as filler. The reference particleboard characteristics used are Indonesian Standard, SNI 03-2105-2006. The characteristics observed were pore diameter, hardness, impact toughness, flexural strength, and thickness development. The particleboard composition is 50% filler, 15% oil palm empty fruit bunches, 20% polyvinyl acetate adhesive, and 15% epoxy resin. The length of fiber used is 5 mm. This research shows that particleboard with mahogany filler has optimum characteristics, namely pore diameter 2.0288 nm, hardness 43 N/mm 2, flexural strength 641.65 N/mm 2, toughness 3.54 kJ/m 2, and thickness swelling 1.20%.